Populism as Synecdochal Representation: Understanding the Transgressive Bodily Performance of South American Presidents - Casullo, María Esperanza (2020)
Fil: Casullo, Maria Esperanza. Universidad Nacional de Río Negro. Río Negro, Argentina.